2008
DOI: 10.1524/ract.2008.1483
|View full text |Cite
|
Sign up to set email alerts
|

An overview and historical look back at the solvent extraction using nitrogen donor ligands to extract and separate An(III) from Ln(III)

Abstract: The partitioning of minor trivalent actinides (An) from lanthanides (Ln) is one of the challenges in the chemical treatment of nuclear waste. The optimal ligand to carry out the separation of An(III) and Ln(III) using solvent extraction has to meet several important criteria: high selectivity towards the solute, chemical and radiolytic stability, stripping possibilities and recycling of the organic phase, high separation factors and good distribution ratio, to name just a few of them. A chronological line can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 33 publications
4
136
0
Order By: Relevance
“…Finally, a new class of heterocyclic N-donor SANEX ligands was developed by Foreman et al [38,39] (Fig. 7) can be found in Geist et al [10,40].…”
Section: Regular Sanexmentioning
confidence: 99%
“…Finally, a new class of heterocyclic N-donor SANEX ligands was developed by Foreman et al [38,39] (Fig. 7) can be found in Geist et al [10,40].…”
Section: Regular Sanexmentioning
confidence: 99%
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that Ln-An separation is a challenging task, since both actinides and lanthanides exist in trivalent oxidation state in the feed solution. The methods developed so far, for the Ln-An separation usually exploits the finer differences in the chemical behavior of lanthanides and actinides towards various ligands [6][7][8][9][10][11][12][13][14][15][16][17]. According to HSAB concept, the lanthanides are classified as hard acids as compared to the trivalent actinides.…”
Section: Introductionmentioning
confidence: 99%